(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article revealed an interesting issue on vibrational internal energy and Helmholtz free energy of metals. The relationship existing between the lateral strain and axial strain was taking into consideration during computation. Vibrational internal energy and Helmholtz free energy of metals was computed and studied based on the theory of free electron approximation using the knowledge of thermodynamic potentials. Computed and theoretically obtained experimental valueof vibrational internal energy and Helmholtz free energy of metals agreed quite well with each other.Vibrational internal energy of metals increases as temperature increasesdue to change in atomic configuration mode and valence electron exchange between ions in metals.Increase in vibrational internal energy of metals as strain increases can be caused by weak electron cohesion and uncertainties regarding the behavior of valence electrons, atomic size, atomic configuration and bonding interaction between the electron in metals. Result obtained for free energy of metals is negative throughout which indicate that there is a better binding between electron in metals. Free energy of metals decreases as temperature increases due to reduction in atomic interaction and bond strength between the interacting electron in metals. Free energy of metals decreases as strain increases.